Edinburgh University Press 2018
DOI: 10.3366/edinburgh/9781474400046.003.0032
|View full text |Cite
|
Sign up to set email alerts
|

The Roots and Ramifications of Narrative in Modern Medicine

Abstract: Narrative became a concept of great versatility and fluidity in the second half of the twentieth century, configuring multi-dimensional understandings and meanings in healthcare. The literary and social theorist Martin Kreiswirth speaks of ‘a massive and unprecedented eruption of interest in narrative and in theorizing about narrative’ in the period, which resulted in stories and fragments of stories gaining significant conceptual traction in many discourses and practices. Not until narrative began to be credi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Due to the influence of different schools of thought, including medical humanities, cultural studies, literary theory, social sciences, feminism, psychoanalysis, the work of Michael Balint, primary and patient-centered care, biopsychosocial medicine, holistic care, and postmodern ideas [ 2 – 7 ], the concept of narrative medicine emerged late in the twenty century in response to the inadequacies of, but not to dispense with, the biomedical model [ 6 – 8 ]. After teaching a multidisciplinary course to general practitioners, practice nurses, health visitors, and other primary care professionals since 1995, Launer found that this narrative approach can be useful for not only mental health problems, but all medical encounters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the influence of different schools of thought, including medical humanities, cultural studies, literary theory, social sciences, feminism, psychoanalysis, the work of Michael Balint, primary and patient-centered care, biopsychosocial medicine, holistic care, and postmodern ideas [ 2 – 7 ], the concept of narrative medicine emerged late in the twenty century in response to the inadequacies of, but not to dispense with, the biomedical model [ 6 – 8 ]. After teaching a multidisciplinary course to general practitioners, practice nurses, health visitors, and other primary care professionals since 1995, Launer found that this narrative approach can be useful for not only mental health problems, but all medical encounters [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we explore another strategy that may help mothers notionally return their baby to their body, this time based on narrative approaches to medicine. Narrative has long been drawn upon in therapeutic contexts, and more recently has been acknowledged in medicine and healthcare as a resource for making sense of complex experience (Hurwitz and Bates 2016), for instance, lending a sense of structure to the "biographical disruption" that is a chaotic illness trajectory (Kleinman 1989) or binding it into meaningful story elements that might otherwise seem meaningless. If, as Verghese attests, "story helps us make sense of events in our lives" (Verghese 2001), then metaphor helps us plumb the depths of these events, allowing the communication of "meanings otherwise elusive" (Charon 2006).…”
Section: Methods: Researcher As Instrumentmentioning
confidence: 99%
“…In this paper, we explore another strategy that may help mothers notionally return their baby to their body, this time based on narrative approaches to medicine. Narrative has long been drawn upon in therapeutic contexts, and more recently has been acknowledged in medicine and healthcare as a resource for making sense of complex experience (Hurwitz and Bates 2016), for instance, lending a sense of structure to the "biographical disruption" that is a chaotic illness trajectory (Kleinman 1989) or binding it into meaningful story elements that might otherwise seem meaningless. If, as Verghese attests, "story helps us make sense of events in our lives" (Verghese 2001), then metaphor helps us plumb the depths of these events, allowing the communication of "meanings otherwise elusive" (Charon 2006).…”
Section: Methods: Researcher As Instrumentmentioning
confidence: 99%